Home advantage in judo: A study of the world ranking list - Ferreira Julio, U.; Gonçalves Panissa, V. L.; Miarka, B.; Yuri Takito, M.; Franchini, E. (Journal of Sports Sciences, 2013)
In 2009, the International Judo Federation established a ranking system (RS) to classify athletes and to distribute the competitor quotas of the Olympic Games. However, the RS does not consider the home advantage. This issue has not been studied in judo, and its implications for the RS have not been determined. The objective was to verify the home advantage in judo in terms of winning a medal or the number of matches won. Therefore, 25 competitions that computed points for the RS in 2009 were analysed. Logistic regression analysis and the Poisson generalised linear model were used for the analyses, which included the relative quality of the athletes. The sample was composed only of athletes who had competed both at home and away. The odds ratio for winning medals was higher for athletes who competed at home for both males and females. The association between the number of matches won and competing at home was significant only for the male athletes. The home advantage was observed in the competitions that used the judo RS. Thus, it is likely that athletes from countries that host competitions using the RS have an advantage in terms of obtaining their Olympic classification.